A Study on Selection of organization for Effective Training Outcome using AHP - Dr. Vijit Chaturvedi, Ms.Gurpreet, Mr. Vinod Kumar (International Journal of Advanced Science and Technology, 2020)
One of the most important challenge before any organisation is to identify the most appropriate company if any function or process has to be outsourced. In context to training when it comes to reviving and brushing up the people capability it is important that the selection of the company ahs to be on the basis of carefully selected parameters. The paper aims to identify the most important factors that affect training effectiveness and the role of Analytical Hierarchical Process in identifying suitable organization for outsourcing the training activities to improvise learning and competencies of the organization. The findings reflect that Need based training, quality and outcome measurement were the most important factors affecting selection. Thus, it helps the organisation to identify and choose amongst the best available service provider when it is about an important dimension like training.